The Impact of Competency-Based Pedagogy on Students’ Motivation and Engagement: An Experimental Study - Mohzana, Mohzana (Yayasan Pendidikan Islam Daarut Thufulah, 2025)
ABSTRACTBackground. Competency-based pedagogy (CBP) has emerged as a transformative instructional approach aligned with 21st-century educational demands, emphasizing the mastery of specific skills and learner autonomy. Despite its increasing adoption, empirical evidence regarding its impact on student motivation and engagement remains limited, especially in higher education contexts. Purpose. This study investigates the impact of CBP on undergraduate students’ motivation and classroom engagement in Indonesia.Method. Using a quasi-experimental pretest-posttest control group design, 120 students were assigned to experimental and control conditions. The CBP group experienced mastery learning, self-paced modules, and formative feedback, while the control group followed conventional lecture methods. Data were collected using validated scales and analyzed with ANCOVA. Results. The results showed significant increases in both motivation and engagement in the CBP group (p < 0.001), with large effect sizes. This study provides empirical validation for the integration of CBP in higher education and highlights its role in enhancing learner autonomy and affective outcomes.Conclusion.This study concludes that competency-based pedagogy positively influences students’ motivational and engagement levels, supporting its integration into curriculum design to foster meaningful and active learning experiences.